TINGKAT PENGETAHUAN DAN SIKAP MEMANDIKAN BAYI DAN MERAWAT TALI PUSAT OLEH IBU POST PARTUM - Sundalangi, Militia Christy Aprilia; Rompas, Sefti S.J.; Meo, Maria Lupita N. (JURNAL KEPERAWATAN, 2020)
Abstract The knowledge and attitude of bathing a baby are very important aspects in parenting work. Also to caring for the umbilical cord is the principal thing to notice by mothers regarding newborn care. Lacking of knowledge and attitude in bathing a baby and caring for the umbilical cord could affect the health of the baby. The purpose of this research is to describe the level of knowledge and attitude of baby bathing and caring for the umbilical cord of post-partum mother in Warisa village of Talawaan district of North Minahasa regency. The research method that was used on this research is descriptive research design with survey method. The sample research used the total population model. The total respondent was 33 respondents of post-partum mothers in the Warisa village of Talawaan district of North Minahasa regency. The results showed that from 33 respondents, there were 13 respondents (39.4%) those who have good knowledge in bathing babies, there were 13 respondents (39.4%) those who have lacking knowledge to caring for the umbilical cord, there were 23 respondents (69.7%) those who have negative attitude in bathing babies and there were 19 respondents (57,6%) those who have a negative attitude in caring for the umbilical cord. Conclusion the results of this research were displayed that there were many levels of knowledge in bathing babies and caring for the umbilical cord of the post-partum in Warisa village of North Minahasa Regency. The author suggests that the health services should have been able to see and maximize the needs of the knowledge level and attitude toward newborn care, specifically in terms of post-partum mothers, in bathing the baby and caring for the umbilical cord by improving the level education for the related issues.Keywords: Knowledge, Attitude, Baby Bathing, Umbilical Cord. Abstrak : Pengetahuan dan sikap memandikan bayi dan merawat tali pusat merupakan hal penting yang harus diperhatikan oleh ibu dalam perawatan bayi baru lahir. Pengetahuan yang kurang serta sikap yang tidak baik dalam memandikan bayi dan merawat tali pusat dapat mempengaruhi kesehatan bayi. Tujuan penelitian untuk mengetahui gambaran tingkat pengetahuan dan sikap memandikan bayi dan merawat tali pusat oleh ibu post partum di Desa Warisa Kecamatan Talawaan Kabupaten Minahasa Utara Metode penelitian ini menggunakan desain penelitian deskriptif dengan metode survey. Sampel penelitian ini menggunakan total populasi yaitu seluruh ibu post partum di Desa Warisa Kecamatan Talawaan Kabupaten Minahasa Utara sebanyak 33 responden. Hasil penelitian menunjkkan bahwa dari 33 responden 13 responden (39,4%) memiliki pengetahuan baik dalam memandikan bayi, 13 responden (39,4%) memiliki pengetahuan kurang dalam pengetahuan merawat tali pusat, 23 responden (69,7 %) memiliki sikap negatif dalam memandikan bayi dan 19 responden (57,6 %) memiliki sikap negatif dalam merawat tali pusat . Kesimpulan, hasil penelitian ini mendapatkan gambaran tingkat pengetahuan memandikan bayi dan merawat tali pusat oleh ibu post partum di Desa Warisa Kecamatan Talawaan Kabupaten Minahasa Utara. Saran, Bagi pihak pelayanan kesehatan yang ada diharapkan dapat melihat dan memaksimalkan kebutuhan tingkat pengetahuan dan sikap perawatan bayi baru lahir lebih khusus dalam hal memandikan bayi dan merawat tali pusat oleh ibu post partum dengan meningkatkan edukasi dalam hal memandikan bayi dan merawat tali pusat.Kata Kunci : Pengetahuan, Sikap, Memandikan Bayi, Merawat Tali Pusat.